994 The Cost of Testicular Torsion Care in Ireland 2009-2018: A Novel Cost Estimation Model Using a National Database. (4th May 2021) - Sugrue, D; Driessen, A
Abstract: Introduction: Activity-Based Funding (ABF) is a new reimbursement model for public hospitals in Ireland. Little data exists regarding cost estimates for acute surgical admissions in Ireland. This study presents a novel method of direct-cost estimation for Testicular Torsion (TT) care in Ireland. Method: Hospital In-Patient Enquiry (HIPE) data, covering all public hospital admissions in Ireland, were analysed to derive annual incidence rates for TT between 2009-2018. The monetary cost of each case was calculated by cross-referencing the Diagnosis-Related Group (DRG) with reference prices for inpatients and day-cases in public hospitals in 2019. Annual cost was adjusted using the Consumer Price Index for Health (Ireland) Results: N = 1, 746 patients under 25 years underwent orchidectomy or orchidopexy for TT between 2009 and 2018. The direct cost of TT care in public hospitals between 2009 and 2018 was €6, 331, 402. Costs increased 54% over 10 years, from €513, 232 in 2009 to €788, 700 in 2018 (2019 Euros). Just over two-thirds of cases (70%, n = 1, 230) were reimbursed with public funding Conclusions: This novel cost-estimation model may serve as a template for future direct-cost estimates for surgical interventions in Ireland. This will improve the accuracy of future economic evaluation for healthcare interventions in Ireland.